2017
DOI: 10.1158/1541-7786.mcr-16-0262
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling in Formalin-Fixed and Paraffin-Embedded Prostate Cancer Tissues

Abstract: Metabolite profiling has significantly contributed to a deeper understanding of the biochemical metabolic networks and pathways in cancer cells. Metabolomics-based biomarker discovery would greatly benefit from the ability to interrogate retrospective annotated clinical specimens archived as formalin-fixed, paraffin-embedded (FFPE) material. Mass spectrometry–based metabolomic analysis was performed in matched frozen and FFPE human prostate cancers as well as isogenic prostate cancer cell lines. A total of 352… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…The use of a single analytical platform could be associated with the detection of small differences in the metabolic profile of OLP clinical forms. Moreover, although metabolomics based on formalin‐fixed paraffin‐embedded tissue is a valuable tool to differentiate biological states, the process of formalin‐fixation with paraffin‐embedding causes a reduction in several classes of metabolites, such as peptides and steroids . Therefore, future metabolomics analyses of fresh frozen specimens are warranted to complement our findings.…”
Section: Discussionmentioning
confidence: 77%
“…The use of a single analytical platform could be associated with the detection of small differences in the metabolic profile of OLP clinical forms. Moreover, although metabolomics based on formalin‐fixed paraffin‐embedded tissue is a valuable tool to differentiate biological states, the process of formalin‐fixation with paraffin‐embedding causes a reduction in several classes of metabolites, such as peptides and steroids . Therefore, future metabolomics analyses of fresh frozen specimens are warranted to complement our findings.…”
Section: Discussionmentioning
confidence: 77%
“…The number of metabolites was similar to results obtained within presented study (157 compounds before filtration). However, the results presented by Cacciatore et al [16] were obtained with the use of two complementary techniques, whereas, in presented research, only one technique was applied. Moreover, authors did not distinguish how many compounds were detected by every applied technique.…”
Section: Application Of the Optimized Sample Preparation Proceduresmentioning
confidence: 68%
“…However, some previously published studies covered the comparison of metabolic profiles obtained from FFPE tissues and fresh-frozen specimens. According to the literature, formalin fixation and paraffin embedding may cause loss of about 25% of detected metabolites when compared to fresh-frozen samples, especially such groups as amino acids, peptides, or carbohydrates [13,15,16]. Fortunately, the goal of our study was to analyze fatty compound synthesis and metabolism, which were found to be stable during FFPE sample preparation procedure.…”
Section: Application Of the Optimized Sample Preparation Proceduresmentioning
confidence: 97%
See 2 more Smart Citations